(untitled) (Swiss Medical Weekly, 2021)
INTRODUCTION Biodiversity has intrinsic value and a fundamental role in human health. The relationship between them is complex, and the specific sustaining processes are still not well understood. In view of the rapidly evolving landscape, this literature review investigated scientific evidence for specific links between biodiversity and human infectious and non-communicable diseases to characterise identifiable relationships. METHODS A search of the PubMed and Web of Science databases using keyword algorithms identified relevant manuscripts published between 1 January 2000 and 18 April 2019. Qualitative data were extracted from 155 studies investigating links between or mechanisms linking biodiversity and infectious disease, non-communicable disease, allergic/inflammatory disease and microbiomes. RESULTS None of the reviewed studies documented causal evidence for a mechanism linking biodiversity and human health. The main mechanisms proposed to link biodiversity and transmission of infectious disease were dilution and amplification. The dilution hypothesis argues that an increase in species diversity leads to a decrease in pathogen prevalence. The amplification effect is the converse, that there is a positive correlation between species diversity and disease risk/infection prevalence. Several driving factors are postulated, including encounter reduction, interspecies competition and predation. In addition, it appears that scale, both spatial and temporal, highly impacts diversity-disease relationships. There is strong evidence that the early environment of a child, including maternally transferred prenatal signals, affects immune maturation, modifying later disease risk. Bi-directional axes communicate between the gut microbiome and the brain, as well as between the skin microbiome and the lung, leading to direct and indirect immune, humoral and neural mechanisms. The main challenges in assessing links between biodiversity and human health are the wide variation in definitions of health and biodiversity, and the heterogeneity in types of studies encountered, as well as the complexity of interactions in dynamic systems. CONCLUSIONS Contextually adapted integrative approaches, which maintain dialogue across disciplines and amongst all stakeholders, are most likely to generate robust evidence. Because of the relevance of local scale, research engagement must occur across levels to generate legitimate practices and translate into sustainable, equitable policies. Recommendations for future action include: improve the knowledge base on contribution of biodiversity to health, increase awareness of health effects of natural and near-natural environments and biodiversity, and promote synergies by increasing policy coherence.